Peran Media Sosial Untuk Meningkatkan Eksistensi Panti Asuhan Di Daerah Terpencil Pada Era Digital - Jerem Korina; Diah Anggeraini Hasri; Muhammad Nur Fietroh; Hartini (Jurnal Inovasi Pengabdian Masyarakat, 2025)
The objectives of this research are : To raise community awareness of the existence of Al-Mizan Orphanage through social media.To develop a web-based information system to facilitate data and information management. And,to improve the quality of education for children in the orphanage by providing learning facilities.The research method used is qualitative with a descriptive approach. Primary data was obtained through interviews, observations, and documentation, which were then analyzed using source triangulation.The results indicate that the effective use of social media significantly enhances the visibility of the orphanage, positively impacting community support and donations. Additionally, the development of the website facilitates access to information and data management. The improvement of learning facilities also contributes to the quality of education for children, as evidenced by their active participation in supplementary learning programs.